The Efficacy of Multifaceted Breastfeeding Promotion Programs on Maternal and Infant Outcomes: A Systematic Review - Ade Rahma Anggraini; Fauzan Azim (International Medical Journal Corp. Ltd, 2025)
Introduction: Despite the well-documented health benefits of breastfeeding for mothers and infants, global rates of exclusive and continued breastfeeding fall significantly short of World Health Organization (WHO) recommendations. This systematic review synthesizes and evaluates the evidence on the efficacy of various breastfeeding promotion programs designed to address this critical public health gap. Methods: A systematic review of randomized controlled trials (RCTs) and cluster-RCTs was conducted. Major electronic databases, including PubMed, Google Scholar, Semantic Scholar, Springer, Wiley Online Library, were searched for studies evaluating any structured intervention aimed at improving breastfeeding outcomes compared to usual care. The methodological quality of included studies was rigorously assessed using the Cochrane Risk of Bias tool. A narrative synthesis of the findings was performed, structured by intervention type, with quantitative data pooled for meta-analysis where appropriate. Results: The evidence from 17 high-quality trials and meta-analyses demonstrates that structured breastfeeding promotion programs yield significant positive effects. Multi-component interventions that combine education with proactive, ongoing support consistently improve rates of exclusive breastfeeding (EBF) at key postpartum intervals, including 4-6 weeks and up to 6 months. Specifically, system-level policies like the Baby-Friendly Hospital Initiative (BFHI) significantly increase EBF at 3 months (43.3% vs 6.4%) and reduce infant gastrointestinal infections (Odds Ratio 0.60). Peer and lay support models are highly effective, increasing breastfeeding duration and exclusivity while reducing infant morbidity. Furthermore, technology-mediated interventions (e.g., mHealth, web-based support) represent a powerful and scalable approach, significantly increasing EBF rates at 6 months (Risk Ratio 1.87) and nearly doubling the median duration of EBF in some trials. Interventions targeting fathers also show substantial benefits, increasing full breastfeeding rates at 6 months (25% vs 15%). Discussion: The synthesized evidence strongly supports a paradigm shift from passive, single-component educational approaches to proactive, multi-faceted, and sustained support systems. The most effective interventions enhance maternal self-efficacy, provide timely and accessible information, and create a supportive ecosystem involving healthcare professionals, peers, and family. Scalable models, including peer counseling and technology-based platforms, offer promising solutions for widespread implementation. Conclusion: Breastfeeding promotion programs are a demonstrably effective public health strategy for improving breastfeeding rates and associated maternal and infant health outcomes. To maximize impact, programs should be structured, continuous, and leverage a synergistic combination of professional, peer, and technological support tailored to the needs of the target population.